Detection of butter adulteration with lard using differential scanning calorimetry - Ahmad Fadzlillah, Nurrulhidayah; Rosman, Arieff Salleh; Abdul Rohman,; Ismail, Amin; Mustafa, Shuhaimi; Khatib, Alfi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Differential scanning calorimetry (DSC) is developed and used for detection of butter adulteration with lard. Butter has the similar characteristics to lard makes lard a desirable adulterant in butter. DSC provides unique thermal profiling for lard and butter. In the heating thermogram of the mixture, there was one major endothermic peak (peak A) with a smaller shoulder peak embedded in the major peak that gradually smoothed out to the major peak as the lard percent increased. In the cooling thermogram, there were one minor peak (peak B) and two major exothermic peaks, peak C which increased as lard percent increased and peak D which decreased in size as the lard percent increased. From Stepwise Multiple Linear Regression (SMLR) analysis, two independent variables were found to be able to predict lard percent adulteration in butter with R2 (adjusted) of 95.82. The SMLR equation of lard percent adulteration in butter is 293.1 - 11.36 (Te A) - 2.17 (Tr D); where Te A is the endset of peak A and Tr D is the range of thermal transition for peak D. These parameters can serve as a good measurement parameter in detecting lard adulteration in butter. DSC is a very useful means for halal screening technique to enhance the authenticity of Halal process.